Mother and Children Literacy Model at Home - Nur Inten, Dinar; Mulyani, Dewi; Aziz, Helmi (KnE Social Sciences, 2023)
The literacy skill of Indonesian children has been ranked below average in the world. In fact, literacy skills are needed by every individual. Therefore, immediate action is needed starting from the closest environment, namely by the family to foster a literate soul in children. In addition, the mother plays a vital role in her child’s life, as she is the one most closest. Therefore, in order to determine a suitable and interesting literacy model for mothers and children, it is necessary to know how to carry out mother and children literacy activities at home. This research aims to examine the implementation of mother and children literacy activities carried out by mothers having elementary and junior high school education backgrounds in Lamajang Village, Bandung Regency. This study uses a descriptive method by collecting data using a questionnaire administered to 20 respondents. The findings show that the most used media in literacy activities at home is story books that have moral and religious messages. However, there has not been any specific method aligning to the children’s development used by the mother. It was found that they chose activities that combined children’s speaking and listening skills. In addition, children’s interest occurred when the stories delivered by the mother involved the children in the creation of a meaningful work. Keywords: learning model, mother and children literacy, home